2018
DOI: 10.1111/trf.15112
|View full text |Cite
|
Sign up to set email alerts
|

Platelet transfusions and mortality in necrotizing enterocolitis

Abstract: BACKGROUND Prior studies have suggested an association between platelet transfusions (PTXs) and worse outcomes among infants with necrotizing enterocolitis (NEC), potentially mediated by proinflammatory factors released by platelets. However, the effects of storage on platelet proinflammatory factor release and the confounding role of illness severity on NEC outcomes have not been determined. STUDY DESIGN AND METHODS First, neuropeptide Y (a potent splanchnic vasoconstrictor released by platelets) was measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 38 publications
3
10
0
Order By: Relevance
“…While these findings might have seemed surprising at first, they were in fact consistent with a number of prior observational studies describing a poor association between severity of thrombocytopenia and bleeding risk (51, 53-55), a lack of effectiveness of platelet transfusions to prevent bleeding in neonates (51, 97), and an association between number of platelet transfusions and neonatal mortality and morbidity (98)(99)(100)(101).…”
Section: Interventions To Manage and Prevent Bleeding In Neonates Plasupporting
confidence: 86%
“…While these findings might have seemed surprising at first, they were in fact consistent with a number of prior observational studies describing a poor association between severity of thrombocytopenia and bleeding risk (51, 53-55), a lack of effectiveness of platelet transfusions to prevent bleeding in neonates (51, 97), and an association between number of platelet transfusions and neonatal mortality and morbidity (98)(99)(100)(101).…”
Section: Interventions To Manage and Prevent Bleeding In Neonates Plasupporting
confidence: 86%
“…This analysis demonstrated that neonates with the highest baseline risk of bleeding/mortality (based on accepted clinical factors such as gestational age, underlying diagnosis, etc) benefitted just as much as low‐risk neonates from the restrictive transfusion thresholds. While these findings seemed surprising at first, they were in fact consistent with several observational studies that had found a poor correlation between platelet count and bleeding risk (suggesting that factors other than platelet count are better predictors of bleeding risk in neonates), 7,11–14 no effect of platelet transfusions in reducing the incidence or severity of IVH, 8,12,15 and an association between number of platelet transfusions and increased neonatal morbidity and mortality 16–22 …”
Section: Thrombocytopenia and Platelet Transfusions In Neonatessupporting
confidence: 78%
“…Multiple observational studies have reported an association between severe anemia and the development of NEC [34][35][36]. Anemia can impair splanchnic perfusion and increase intestinal inflammation and barrier disruption leading to tissue hypoxia and anaerobic metabolism and thus predisposing to ischemic injury and possibly to NEC [37][38][39][40]. Thus, preventing anemia could be a strategy to prevent the development of NEC, and RBC transfusion is a commonly used method to achieve this [41,42].…”
Section: Discussionmentioning
confidence: 99%